Metabolic reprogramming in macrophage responses - Yang Liu; Ruyi Xu; Huiyao Gu; Enfan Zhang; Jianwei Qu; Wen Cao; Xi Huang; Haimeng Yan; Jingsong He; Zhen Cai (BMC, 2021)
Abstract Macrophages are critical mediators of tissue homeostasis, with the function of tissue development and repair, but also in defense against pathogens. Tumor-associated macrophages (TAMs) are considered as the main component in the tumor microenvironment and play an important role in tumor initiation, growth, invasion, and metastasis. Recently, metabolic studies have revealeded specific metabolic pathways in macrophages are tightly associated with their phenotype and function. Generally, pro-inflammatory macrophages (M1) rely mainly on glycolysis and exhibit impairment of the tricarboxylic acid (TCA) cycle and mitochondrial oxidative phosphorylation (OXPHOS), whereas anti-inflammatory macrophages (M2) are more dependent on mitochondrial OXPHOS. However, accumulating evidence suggests that macrophage metabolism is not as simple as previously thought. This review discusses recent advances in immunometabolism and describes how metabolism determines macrophage phenotype and function. In addition, we describe the metabolic characteristics of TAMs as well as their therapeutic implications. Finally, we discuss recent obstacles facing this area as well as promising directions for future study.